Disseminating and Using Student Assessment Information in Chile - Ramírez, María-José (World Bank, Washington, DC, 2014)
Student assessment plays a key role in improving education. However, many countries do not disseminate and make effective use of their student assessment information. This paper discusses Chile's effective use of its assessment information and draws lessons for other countries. A key lesson from the Chilean experience is that effective use of assessment information is a challenging task that takes time, effort, and resources. Another lesson is that the task requires leadership, long term planning, and consensus building. Countries able to learn from Chile's lessons will be in a better position to make effective use of their student assessments and, ultimately, to contribute to education quality and learning.